Exploring the Use of Instrumented Insoles to Estimate Trunk Local Dynamic Stability During Treadmill Walking - Mir-Orefice, Alexandre (Université d'Ottawa / University of Ottawa, 2023)
Gait assessments can help identify individuals at an elevated risk of falling. Gait variability and local dynamic stability (LDS) are considered the most valid measures to assess gait stability and predict gait-related falls. Specifically, LDS of the trunk is most often used to assess gait stability given its important contribution to the centre of mass and the ability to discriminate between fallers and non-fallers using its kinematics. Reliable wearable sensors can be implemented in real-world gait assessments to actively screen for fall risk. Instrumented insoles are an example of unobtrusive wearable technology that can perform accurate gait assessments in real-world settings; however, they have not been validated for gait stability assessments, and cannot directly measure trunk LDS. The purpose of this thesis was to develop a framework to estimate gait stability using instrumented insoles. Fifteen participants were recruited to walk on a treadmill for seven minutes at their preferred walking speed while wearing instrumented insoles and a full-body inertial measurement unit suit. The reliability of foot LDS calculated from instrumented insole data was evaluated against the inertial measurement unit suit using intraclass correlation coefficients. Trunk LDS, measured via the IMU suit, was then predicted by applying linear regressions to the insole-derived metrics. A simple linear regression was used to establish the base amount of variance in trunk LDS that could be explained by foot LDS. Subsequently, a multiple linear regression model consisting of the standard deviation of stride time, standard deviation of double support time, mean single support time, mean yaw variability, and median absolute deviation of yaw variability was used to estimate trunk LDS. Results show that instrumented insoles can reliably measure foot LDS (ICC₃,₁ = 0.860). Moreover, the multiple linear regression explained 47.7% more variance than the simple linear regression (adjusted R² of 0.845 versus 0.368). This thesis demonstrates that instrumented insoles are an appropriate measurement tool for foot stability and that they can be used to predict trunk LDS with good accuracy during gait.
Keywords: Instrumented insoles; Local dynamic gait stability; Gait variability; Biomechanics